The Covid-19 Pandemic and the Rights of the Individual in Terms of Private and Public Law - Kharytonov, Evgen; Kharytonova, Olena; Kolodin, Denis; Tkalych, Maxym (Universidad Hemisferios, 2020)
The principles of adjusting the regulation of civil relations in the context of the Covid-19 pandemic are analyzed. The admissibility of restricting human rights in the context of the conflict of private and public interests are researched. Besides, the authors tried to determine the optimal algorithm of government actions aimed at preventing the spread of the epidemic. The main approach to the understanding of human rights in the article is based on Dworkin's concept of